Evaluación de los residuos agrícolas (Zea mays) y (Musa sapientum) como parte de la economía circular - Mero Ortiz, Alex Alipio (2022)
The objective of this research work was to evaluate agricultural residues (Zea mays) and (Musa sapientum) as part of the circular economy in Calceta, Bolívar canton, Manabí province, the CIIDEA study area was characterized within the polytechnic campus, using ARCGIS version 10.5 software, a map of land use and vegetation cover was made. For the elaboration of the silage, a completely randomized design (Simple DCA) was used, the factors were residues of corn (30 g, 40 g, 50 g per treatment) and banana (60 g 50 g, 40 g per treatment) with a constant variable of 10 g of whey, variables such as: dry matter %, crude protein %, nitrogen, acid detergent fiber %, neutral detergent fiber %, among others, were measured. For the statistical analysis, Anova tests and Tukey's tests were performed (p <0.5), where it was determined that any treatment can be used, however, the treatment that is in the best conditions is T3 with 50% corn., banana 40% and whey 10%. Once the silage was prepared, it was applied to the diet of hens (Gallus domesticus L), weight and mortality were observed in the birds. For the analysis of the cost of production of a kilo of silage, the results of the study were used as a basis to detail the unit price, starting as a unit a micro silage silo of 1 kg, obtaining a final cost per kilo of $0,51.